First-principles study on the stability and properties of β-SiC/Mn+1AlCn (M=Sc, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta; n=1, 2) interfaces. (April 2019) - Zhang, Xiaohong; Li, Yifan; Qiao, Yingjie; Chen, Hailong; Wang, Yi; Germann, Timothy C.; Huang, Qing; Bai, Xiaojing; Zhou, Xiaobing; Guo, Yaolin; Luo, Kan; Du, Shiyu
Abstract: In this work, first principles calculations are performed to investigate the structural, electronic, and mechanical properties of the interface between β-SiC ceramics and M n +1 AlC n (M = Sc, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta; n = 1, 2) phases, with particular focus on Ti3 AlC2 and Ti2 AlC. The interface between the β-SiC(111) and Ti n+1 AlC n (0001) ( n = 1, 2) surfaces is most likely a stable interface because of the small misfit in lattice constants. Six different interface models between β-SiC(111) and Ti n +1 AlC n (0001) are examined. The optimized interfacial distances are determined using the universal binding energy relation method, and then each model is fully relaxed to calculate work of adhesion. By comparison, it is determined that the junctions connecting the C-terminated SiC(111) and Ti-terminated Ti n +1 AlC n (0001) surfaces are the most stable structures. Then the electronic structures for this interface model of Ti3 AlC2 /SiC are analyzed from the density of states, atomic charges, total electron densities and electron density difference. The elastic moduli are also computed in this study, and the data show that the mechanical properties for the composite Ti n +1 AlC n /SiC slab are between those of bulk Ti n +1 AlC n and β-SiC, with enhanced plasticity. Finally, the results for β-SiC/Ti n +1 AlC n are extended to study the interfacial stabilization of β-SiC ceramics and the wider class of M n +1 AlC n phase coatings (M = Sc, Ti, V, Cr, Zr, Nb, Mo, Hf, Ta; n = 1, 2). It is found that SiC ceramics may be effectively joined by M n+1 AlC n with stable interfacial chemical bonding, which provides a theoretical basis for the effective junction in SiC composites. Highlights: The first-principles method is used to determine the structures and energetics of the Ti n+1 AlC n (n=1, 2)/SiC interface. The characteristics of the interfacial bonding and elastic mechanical properties for the Ti3 AlC2 /SiC model are examined. The stable interfacial structures formed between M n+1 AlC n (0001) and SiC(111) have been explored computationally.